Android App for Information of Food Additives Contained in Packaged Foods - Umi Sa'adah; Tita Karlita; Muchammad Arfian (Institut Teknologi Sepuluh Nopember, 2014)
Today, the usage of food additives can be found in nearly every food, especially in packaged foods. Meanwhile, the majority of people are unaware of the impact of the use of food additives in the human body when consumed freely. One of the easiest ways to determine the ingredients of a packaged food, is to read the label of product composition. If it is doubtful, then the product was not consumed. However, public knowledge about food ingredients listed in the product composition is generally relatively low. So, even if they could determine the ingredients of the packaged food products, but still do not know the impact of their use. In this research, built an Android app of Food Additives Glossary that presents information about each type of food additives. This app has a barcode scanner and decoder using ZXing library to facilitate the acquisition of data from the food additives listed in packaged foods. User reads the barcode of packaged food products using the barcode scanner. This applications will display of food additives contained therein. Furthermore, the user can select one of the food additives and the application will display some information, such as: INS code, category (safety, unhealthy, dangerous), ADI (Acceptable Daily Intake) limits, side effects and further description of the food additives.